2019
DOI: 10.1021/acsomega.9b02751
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Naringin in GelMA-Incorporated Rutile Nanorod Films to Regulate Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: Naringin, a Chinese herbal medicine, has been demonstrated to concentration-dependently promote osteogenic differentiation of mesenchymal stem cells (MSCs). However, it remains a challenge to load naringin on coatings for osteogenesis and further control the release kinetics. Here, we demonstrated that the release behavior of naringin on rutile nanorod films could be controlled by either mixing naringin with gelatin methacryloyl (GelMA) before spinning onto the films or soaking the obtained GelMA-incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…At 72 h, less than 10% of naringin remained in GelMA-N compared to more than 45% in nanocomposite hydrogels. The obtained release profiles of GelMA and nanocomposite GelMA are comparable to those obtained in the literature for naringin and other therapeutic molecules [ 42 , 60 , 61 ]. This suggests that GelMA scaffolds can be successfully loaded with LipoN and provide a controlled extended release of the encapsulated flavonoid, which might improve its in vivo bioavailability and hence its therapeutic effect.…”
Section: Resultssupporting
confidence: 82%
“…At 72 h, less than 10% of naringin remained in GelMA-N compared to more than 45% in nanocomposite hydrogels. The obtained release profiles of GelMA and nanocomposite GelMA are comparable to those obtained in the literature for naringin and other therapeutic molecules [ 42 , 60 , 61 ]. This suggests that GelMA scaffolds can be successfully loaded with LipoN and provide a controlled extended release of the encapsulated flavonoid, which might improve its in vivo bioavailability and hence its therapeutic effect.…”
Section: Resultssupporting
confidence: 82%
“…Second, our study revealed that NG showed better osteogenesis than CGRP did in some of the groups. The reason might be that NG has anti‐inflammatory properties that can promote the osteoblast process (Shao et al, 2019; Yin et al, 2015). According to these results, 3D bioprinting scaffolds can be fabricated to elucidate the functions of promoting soft and hard tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 54 The morphologies of the MSCs/ECs in PG/PGM were observed using a scanning electron microscope (Nova Nano 450, FEI, USA) as described in our previous study. 55 ECs were fixed in 4% paraformaldehyde (Biosharp, China) and stained with a mouse anti-CD31 monoclonal antibody (Abcam, UK), rhodamine-phalloidin (Cytoskeleton, USA), and DAPI (Vector, USA).…”
Section: Methodsmentioning
confidence: 99%